Impaired ankle inversion proprioception during walking is associated with fear of falling in older adults - Shao, Xuerong; Wang, Zheng; Luan, Lijiang; Sheng, Yilan; Yu, Ruoni; Pranata, Adrian; Adams, Roger; Zhang, Anren; Han, Jia (Frontiers in Aging Neuroscience, 2022)
Background: Ankle proprioception plays a critical role in lower limb movement control. However, the relationship between ankle proprioception and fear of falling (FOF) in older people is still unclear. Objective: (1) To develop a new device for measuring ankle inversion proprioceptive discrimination sensitivity during walking, i.e., the Ankle Inversion Discrimination Apparatus - Walking (AIDAW), and assess the test-retest reliability of the AIDAW in both young and older adults; (2) To evaluate the discriminant validity of the measure by comparing ankle proprioception during walking between the two groups; and (3) To explore convergent validity by determining to what extent the AIDAW proprioceptive scores correlate with Fall Efficacy Scale-International (FES-I) scores. Methods: The AIDAW was purpose-built to test ankle inversion proprioceptive discrimination sensitivity during walking. The Area Under the Receiver Operating Curve (AUC) was calculated as the proprioceptive discrimination score. Fifty-four adults volunteered. Test-retest reliability was evaluated in 12 young and 12 older adults, and another 15 young and 15 older adults completed the comparison study. FOF was assessed by using the FES-I. Results: The test-retest reliability intraclass correlation coefficient ICC (3,1) value for the whole group was 0.76 (95% CI: 0.52-0.89). The ICC values of the young and older groups were 0.81 (95% CI: 0.46-0.94) and 0.71 (95% CI: 0.26-0.91), respectively. The Minimal Detectable Change with 90% confidence (MDC90) values for the young and older groups were 0.03 and 0.11, respectively. There was a significant difference between the AIDAW proprioceptive sensitivity scores for the young and older groups (0.78±0.04 vs.0.72±0.08, F=5.06, p=0.033). Spearman correlation analysis showed that the FES-I scores were significantly and negatively correlated with the AIDAW scores (rho=-0.61, p=0.015), with higher FOF associated with worse ankle proprioception. Conclusion: The AIDAW is a reliable and valid device for the measurement of ankle proprioception during walking in both young and older adults. Ankle inversion proprioceptive discrimination sensitivity during walking was found to be impaired in the elderly compared to young adults. This impairment was found to be strongly associated with FOF, suggesting that both assessment of and intervention for ankle proprioception in this population are needed to reduce risk of falls.